Understanding love philosophy, film, and fiction (Oxford University Press, 2014)
"This collection of original essays, written by scholars from disciplines across the humanities, addresses a wide range of questions about love through a focus on individual films, novels, plays, and works of philosophy. The essays touch on many varieties of love, including friendship, romantic love, parental love, and even the love of an author for her characters. How do social forces shape the types of love that can flourish and sustain themselves? What is the relationship between love and passion? Is love between human and nonhuman animals possible? What is the role of projection in love? These questions and more are explored through an investigation of works by authors ranging from Henrik Ibsen to Ian McEwan, from Rousseau to the Coen Brothers." -- Publisher's description.